Late Holocene glacial activity in Manatee Valley, southern Coast Mountains, British Columbia, Canada - Koehler, Lindsey; Smith, Dan J. (Canadian Journal of Earth Sciences, 2011)
The dendroglaciologic and lichenometric research methodologies employed in this study provide a perspective of glaciological conditions from 5 ka to present in a remote headwater area of the British Columbia Coast Mountains. Since Holocene ice fronts of four glaciers at this site periodically extended below treeline, previous glacier advances overrode and buried forests beneath till deposits. This study suggests that glaciers were expanding into standing forests at 4.76 and 3.78 ka. Following glacier expansion at 3.78 ka, a period of recession ensued when glaciers withdrew upvalley long enough for the development of deep pedogenic surfaces and the growth of trees exceeding 300 years. Investigations at Beluga and Manatee glaciers benchmark a subsequent episode of significant glacial expansion at 2.42 ka referred to as the “Manatee Advance”. This advance has regional correlatives and is distinguished from the Tiedemann Advance at Manatee Glacier by documentation of substantive ice front retreat between the two episodes. Examination of Little Ice Age (LIA) deposits in the study area allowed for presentation and application of a revised Rhizocarpon spp. lichen growth curve. Lichenometric surveys of lateral moraines associated with Beluga, Manatee, and Oluk glaciers provided limited insight into their early LIA behaviour but record advances during the 15th and 16th centuries. Locally, glaciers achieved their maximum LIA size prior to an early to mid 18th century moraine-building event. This reconstruction of Holocene glacial history offers insights consistent with the emerging record of glacier activity described for other southern British Columbia Coast Mountain glaciers.